2020
DOI: 10.1007/s00122-020-03702-0
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic marker kit for Fusarium wilt and sterility mosaic diseases resistance in pigeonpea

Abstract: Fusarium wilt (FW) and sterility mosaic diseases (SMD) are key biotic constraints to pigeonpea production. Occurrence of these two diseases in congenial conditions is reported to cause complete yield loss in susceptible pigeonpea cultivars. Various studies to elucidate genomic architecture of the two traits have revealed significant marker–trait associations for use in breeding programs. However, these DNA markers could not be used effectively in genomics-assisted breeding for developing FW and SMD resistant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 54 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Multiple QTLs conferring resistance to PPSMV have been identified in pigeonpea, but as in this study, candidate genes have not been identified [30,31]. However, a Kompetitive allele-specific PCR (KASP) assay has recently been designed to aid in the identification of PPSMV-resistant pigeonpea varieties [32]. If the markers in this study that distinguish haplotypes 5B and 1D can be validated, similar marker tests could be deployed in roses to track and manipulate a given QTL and identify progeny likely to have reduced susceptibility to RRD.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple QTLs conferring resistance to PPSMV have been identified in pigeonpea, but as in this study, candidate genes have not been identified [30,31]. However, a Kompetitive allele-specific PCR (KASP) assay has recently been designed to aid in the identification of PPSMV-resistant pigeonpea varieties [32]. If the markers in this study that distinguish haplotypes 5B and 1D can be validated, similar marker tests could be deployed in roses to track and manipulate a given QTL and identify progeny likely to have reduced susceptibility to RRD.…”
Section: Discussionmentioning
confidence: 91%
“…Seq-BSA has provided 7 candidate SNPs for FW and SMD resistance in pigeonpea which are useful for the genomics-assisted breeding in pigeonpea [108]. A diagnostic marker kit was developed with 10 markers for identification of SMD resistant lines [109]. A 50 hypervariable pigeonpea specific simple sequence repeat (AHSSR) markers were screened to identify genomic regions associated with resistance to SMD through bulk segregant analysis (BSA) approach in 84 RILs derived from a cross ICP 8863 (S) x BRG 3 (R).…”
Section: Application Of Molecular Markersmentioning
confidence: 99%
“…Furthermore, Super Annigeri-1, an improved version of Annigeri- 1, and “Pusa Chickpea Manav” were developed by introgressing resistance for Fusarium wilt through MABC approach was successfully released in India ( Mannur et al, 2019 ; https://icar.org.in/content/development-two-superior-chickpea-varieties-genomics-assisted-breeding ; https://www.icrisat.org/genomics-assisted-breeding-delivers-high-yielding-wilt-resistant-chickpea-for-commercial-cultivation-in-central-india/). Efforts are underway in pigeonpea for introgressing resistance to Fusarium wilt and sterility mosaic disease ( Saxena et al, 2020 ).…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%